Una estrategia de supervivencia familiar en Barcelona, en la segunda mitad del siglo XIX - Ana María Rodríguez Martín (Centre de Recherches sur les Mondes Américains, 2008)
This article focuses on the whereabouts of the parents and their legitimate children left before the Barcelona foundling-hospital in the second half of the 19th century. The recovery of those children by their parents after some time is also studied, as well as the evolution of that foundling-hospital, which went from only caring for foundlings to accepting children from families with problems.